Histological aspects and structural characteristics of the testes of Dendropsophus minutus (Anura, Hylidae) - Santos, Lia Raquel de Souza [UNESP]; Oliveira, Classius de [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
The present study describes morphological aspects of testes and presents a general characterization of the seminiferous elements of Dendropsophus minutus (Peters, 1872). Twenty samples of the species were used; after macroscopic descriptions the testes were submitted to histological routine for microscopic analysis. Anatomically, the testes measured 1.90 +/- 0.13 torn, and were oval and milky-white. In relation to microscopic aspects, it was observed in D. minutus, as well as in anuran amphibians, that spermatogenesis occurs in the seminiferous tubule where elements of the germ epithelium are organized in spermatogenetic cysts. Each cyst contains cells in the same stage of differentiation. Characterization of each cellular type enables the identification and differentiation of germ lineage cells. Spermatogonia 1, found at the epithelial base, are the largest of the lineage cells and are usually present in association with Sertoli cells present next to the basal membrane. During the mitotic proliferation phase, cysts containing variable numbers of spermatocytes II are originated; these spermatocytes are smaller and similar inside the cyst. Spermatocytes I are developed after some morphological changes; these spermatocytes are large cells with a spherical nucleus and different degrees of nuclear compaction. Spermatocytes II, highly numerous cells resultant from the first meiotic division, are much smaller than their antecedents. A second meiotic division produces haploid cell formation, specifically spermatids I, which through cellular differentiation form spermatids II. Spermatids II are elongated and organized in bundles supported by Sertoli cells. Spermatozoids appear during the spermiogenesis process and in their most advanced stage they lose their fascicular organization and are released in the tubular lumen, where they follow a pathway through the duct system. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Reproduction; Morphology; Spermatogenesis; Germinative cells; Testes; Anura; Dendropsophus minutus